Running, walking, and hyperventilation causing asthma in children. - Kilham, H (1979)
To examine further the relation between type of exercise, workload, ventilation, and exercise-induced asthma, we compared treadmill walking with treadmill running and treadmill running with isocapnic hyperventilation in separate studies in children and adolescents. Inspired air conditions were identical during each pair of tests. Walking and running with similar minute ventilation and oxygen consumption were followed by similar falls in peak expiratory flow rate as were running and hyperventilation with similar minute ventilation and end-tidal carbon dioxide tension. This study supports the concept that hyperventilation is a central mechanism in exercise-induced asthma.